UNIVERSITY LAND MANAGEMENT: A REVIEW - Muhamad Nur Fadhli Minhat; Nur Berahim; Norhidayah Md Yunus; Ainur Zaireen Zainudin; Siti Radiaton Adawiyah Zakaria; Aminah Mohsin; Tan Liat Choon (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The public universities has recently struggled to maintain its operating costs due to a reduction in budget allocation from Federal Government. As a result, public universities must diversify their revenue sources in order to maintain their operating costs. One initiative that could be taken is through effectively manage the university assets in which land is one of the important components. Land is one of the tangible assets that needs for a systematic operational in a way to achieve assets greatest return. Therefore university as landowner must ensure that their land is strategically and efficiently managed, in order to achieve the best and highest return. The land management theory has emphasis on putting land into efficient use and good effect. Land policy, land information, and land administration are the three components of land management that put land use for good effect. These three components are important to ensuring that land management meets its objectives. Therefore, the main aim of this study is to review on how university managing their land and what are the essential component that supports good land management practice in University. To achieve this, qualitative method used in this research in which it will rely on the analysis of the relevant statutes, university’s strategic plan of the university, the policy and procedure of university land management, journal and book are reviewed to identify the information and practice on university land management. This Study found four component of university land management which are land management unit, land information management, the statement of strategic plan, policy and procedures as well as financial management. These components should be useful for universities especially to their decisions-makers, such as chancellors and asset managers.